Stabilization of Metastable Indomethacin α in Cellulose Nanocrystal Aerogel Scaffolds - Manali Banerjee; Blair Brettmann (MDPI AG, 2021)
Indomethacin (IM) is a small molecule active pharmaceutical ingredient (API) that exhibits polymorphism with the γ-form being the most thermodynamically stable form of the drug. The α-form is metastable, but it exhibits higher solubility, making it a more attractive form for drug delivery. As with other metastable polymorphs, α-IM undergoes interconversion to the stable form when subjected to certain stimuli, such as solvent, heat, pH, or exposure to seed crystals of the stable form. In this study, IM was crystallized into cellulose nanocrystal aerogel scaffolds as a mixture of the two polymorphic forms, α-IM and γ-IM. Differential scanning calorimetry (DSC) and Raman spectroscopy were used to quantitatively determine the amount of each form. Our investigation found that the metastable α-IM could be stabilized within the aerogel without phase transformation, even in the presence of external stimuli, including heat and γ-IM seed crystals. Because interconversion is often a concern during production of metastable forms of APIs, this approach has important implications in being able to produce and stabilize metastable drug forms. While IM was used as a model drug in this study, this approach could be expanded to additional drugs and provide access to other metastable API forms.